(untitled) (American Journal of Smart Technology and Solutions, 2025)
AI and RPA technologies has become the latest trends in the business world that have revolutionized the business sectors at an unprecedented pace. Even though, nowadays AI technologies apply to manufacturing, logistics, supply chain management industries and others, the extent of their benefits on operational capabilities, decision-making procedures, and organizational performance still does not receive enough empirical research attention. To this end, this paper seeks to fill this gap by explaining how AI and automation, more specifically RPA and cognitive automation are changing business processes. In specific, the study focuses on the general application of AI in increasing productivity and efficiency as well as reducing human error occurrences in industries that consist of automated systems. The study uses Random Forest regression and classification models to analyze current data from robotic structures to improve production line performance in manufacturing firms. This paper proves that AI automation helps in enhancing all the time prediction processes and also cooperates with the decision-making process by eradicating operations and decreasing the odds in the course of error. Thus, the outcomes indicate a need to combine new technologies like blockchain and 5G to strengthen the security component, develop efficient data management, as wel l as real-time analysis – all of which expand AI possibilities. Thus, based on the analysis of such trends as cognitive automation, decision making, and maintenance this paper discusses how AI can transform businesses. In addition, it identifies factors affecting implementation in organizations including workforce changes, data issues, and input data that is of poor quality. It also offers a practical set of suggestions for organisations concerning with shifting AI landscape, it also gives consideration of the moral issues and social impacts of AI technology in its discussion.